The core and significance of “Extensive reading” in teaching English as a foreign language in the development of students ' reading skills - H.D.Suvanova (Genius Journals, 2022)
This article is devoted to showing the importance of “Extensive reading” for learners of English as a foreign language through an analysis of the results of scientific research conducted by various scientists to what extent it are important. In addition, the relevance of this reading skill is summarized on the basis of the basic principles. That is, the principles analyzed are based on the results obtained by language learners from ER.
Keywords: Language skills; extensive; reading; teacher